Research projects in the consolidation of the research line: qualification of pedagogical practice in the Spanish language - Navarro Monsalve, Yolanda; Socorro Albarracín, Alba; Tellez de Rojas, Alicia (Rastros Rostros, 2002)
As a result of the academic process that is being developed with all the teachers of the Early Childhood Education and Basic Education programs with emphasis in Spanish and English, spaces arise to think of ourselves as a Cooperative University that trains teachers with political, creative and solidary criteria. It is a task that demands commitment and sense of belonging to the institution, aspects that have characterized the administrative staff, management, teachers and students of the University.